2008
DOI: 10.1001/archsurg.143.5.476
|View full text |Cite
|
Sign up to set email alerts
|

Implications and Management of Pancreatic Fistulas Following Pancreaticoduodenectomy

Abstract: Main Outcome Measures: Development of a pancreatic fistula (defined as Ͼ30 mL of amylase-rich fluid from drains on or after postoperative day 7, or discharge with surgical drains in place, regardless of amount); the need for additional interventions or total parenteral nutrition; other morbidity; and mortality.Results: Seventy-five patients (12.9%) developed a pancreatic fistula. Fistulas were managed with gradual with-drawal of surgical drains. This allowed for patient discharge and eventual closure at a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 24 publications
1
77
0
1
Order By: Relevance
“…However, the morbidity rate still remains in the range of 30-50% [1][2][3], and postoperative pancreatic fistula (POPF) is the most common complication of pancreaticoduodenectomy, which would lead to not only prolongation of the hospital stay but also lethal morbidity or surgical mortality. The incidence of POPF is reported to be 0-17% base on a variety of definition of pancreatic fistula [4][5][6]. Recently, an international study group of pancreatic fistula (ISGPF) defined POPF by reviewing numerous reported series [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the morbidity rate still remains in the range of 30-50% [1][2][3], and postoperative pancreatic fistula (POPF) is the most common complication of pancreaticoduodenectomy, which would lead to not only prolongation of the hospital stay but also lethal morbidity or surgical mortality. The incidence of POPF is reported to be 0-17% base on a variety of definition of pancreatic fistula [4][5][6]. Recently, an international study group of pancreatic fistula (ISGPF) defined POPF by reviewing numerous reported series [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic anastomotic leak remains the leading cause of morbidity with an incidence reaching 20% even in specialized centers [13][14][15][16][17]. Complicated pancreatic anastomotic leak may lead to sepsis and hemorrhage with a mortality rate of up to 40% [8,13,14,18].…”
Section: Discussionmentioning
confidence: 99%
“…Most pancreatic leaks have been reported as a complication occurring within 10 days postoperatively [5,11,19]. The presentations of late leaks have been reported as occult fistula [16] within a few months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Other major causes of morbidity are myocardial infarction (1.5%), epicarditis (2.7%), pulmonary complications (7.9%), thrombosis (6.4%), empyema (2.4%), technical (6.1%) and gastrointestinal complications (0.9%). When performed at an experienced, high-volume center, extrapleural pneumonectomy is associated with a perioperative mortality of between 2.2 and 7% [4][5][6][7][8][9][10], comparable to mortality for other oncologic surgeries, for example, esophagectomy [11], pancreaticoduodenectomy [12,13] and hepatectomy [14].…”
Section: Perspectivementioning
confidence: 99%